2022
DOI: 10.1111/jce.15430
|View full text |Cite
|
Sign up to set email alerts
|

A real‐world experience of atrioventricular synchronous pacing with leadless ventricular pacemakers

Abstract: Aims: The Micra TM transcatheter pacing system (TPS) (Medtronic) is the only leadless pacemaker that promotes atrioventricular (AV) synchrony via accelerometer-based atrial sensing. Data regarding the real-world experience with this novel system are scarce. We sought to characterize patients undergoing Micra TM -AV implants, describe percentage AV synchrony achieved, and analyze the causes for suboptimal AV synchrony. Methods:In this retrospective cohort study, electronic medical records from 56 consecutive pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…Of these articles, 75 studies related to leadless pacemakers were excluded because they did not report atrioventricular synchrony or combined other interventions, and 4 studies because they used the same cohort as other included studies. Ultimately, eight studies met the inclusion criteria for the meta-analysis [ 6 , 7 , 8 , 9 , 10 , 14 , 15 , 16 ]. The PRISMA flow chart is displayed in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these articles, 75 studies related to leadless pacemakers were excluded because they did not report atrioventricular synchrony or combined other interventions, and 4 studies because they used the same cohort as other included studies. Ultimately, eight studies met the inclusion criteria for the meta-analysis [ 6 , 7 , 8 , 9 , 10 , 14 , 15 , 16 ]. The PRISMA flow chart is displayed in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…This approval substantially broadened the spectrum of patients eligible for leadless pacing. Subsequently, several observational studies reported on the early experience with this novel technology in patients with different pacing indications, including atrioventricular block, sinus node dysfunction, and atrial fibrillation with bradycardia [ 8 , 9 , 10 ]. However, the results of these studies varied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 In this study, 95% of patients had >70% AV synchrony at rest. 3 However, 2 previous retrospective studies about Micra AV 4 , 5 demonstrated that only 65% of the patients had >70% AV synchrony, especially during a higher heart rate. These studies showed the importance of appropriate patient selection for the Micra AV and the importance of active device programming.…”
Section: Introductionmentioning
confidence: 95%
“…10 With extensive programming optimization, the proportion of patients in whom AV synchrony can be achieved at rest with this technology can reach 65%-95%. 11,12 However, AV synchrony is lost during physical activity as the device switches to VVI-R mode at higher heart rates. Therefore, in its current iteration, this technology is not expected to provide major incremental benefits in exercise tolerance or performance over single-chamber leadless pacemakers.…”
Section: Follow-upmentioning
confidence: 99%